Wybrane metody szacowania składek w ubezpieczeniach komunikacyjnych OC - Szymańska, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The foundation of insurance activity is the correct estimation of insurance premiums. The premiums should be estimated so that the insuring company would not incur losses and the insured would not pay too much or too little.The overall premium is the net premium enlarged by the security loading and insurance activity costs. In the paper two methods of premium estimation are compared: the expected value method and the variance method. It was also investigated if estimating premiums by means of selected methods allows to build optimal bonus-malus system. The investigation was carried out a real data from a Lodz insurance company. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 305-311